Prevalence and predictors of coronary heart disease among individuals with and without obesity in North Dakota. - Emmanuel Angmorteh Mensah; Md Marufuzzaman Khan; Agricola Odoi; Grace Njau; Matthew Schmidt; Jennifer Lord (PLoS ONE)
Introduction Coronary heart disease (CHD) is the most common cardiovascular disease in the United States and heart disease is the leading cause of death in North Dakota. Although obesity is a major risk factor for CHD, some studies have reported an inverse relationship between body mass index (BMI) and CHD outcomes. Understanding the epidemiology of CHD among individuals with and without obesity is essential to guide health planning. Therefore, the objectives of this study were to estimate the prevalence and identify predictors of CHD among North Dakota adults with and without obesity. Methods Behavioral Risk Factor Surveillance System data from 2017 to 2021 were provided by the North Dakota Department of Health and Human Services. Weighted prevalence estimates and 95% confidence intervals (CIs) were computed for CHD and potential risk factors among respondents with and without obesity (BMI ≥30 kg/m2). Multivariable logistic regression was used to identify significant predictors of CHD in both groups. Results A total of 17,092 respondents were included in the study. Respondents with obesity had a higher prevalence of CHD (4.7%, 95% CI: 4.2-5.4) than those without obesity (3.0%, 95% CI: 2.7-3.4). Predictors of CHD among both groups included age, sex, self-reported general health, high blood pressure, high cholesterol, chronic obstructive pulmonary disease, and diabetes. Having a personal doctor (Odds Ratio [OR] = 1.91, 95% CI: 1.13-3.23) and arthritis (OR = 1.72, 95% CI: 1.34-2.22) were significant predictors of CHD among respondents without obesity, but not among those without obesity. Conclusion While the prevalence of CHD was significantly higher among adults with obesity compared to those without obesity, the findings of the stratified analysis indicated that predictors of the condition tended to be similar for the two groups. This study provides useful information to guide health planning and control programs that aim to reduce the burden of CHD in North Dakota.